The effect of compressing secondary schooling on higher education decisions - Vaishali Zambre; Jan Marcus (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
A major education reform in Germany reduced the length of the academic high school track by one year, while leaving the number of overall instruction hours unchanged. Accordingly, the fixed number of instruction hours was distributed over fewer years of schooling, such that learning intensity and weekly workload increased. We investigate the consequences of this so-called G8 reform on students' higher education decisions. Based on a difference-in-differences approach using high-quality, administrative data on all students in Germany, we find that the G8 reform not only resulted in delayed university enrollment, but also in decreased enrollment rates. Moreover, students are more likely to drop out of university and change their major. The results of our study are not only informative for the German context but also for policy makers in many other OECD countries, trying to increase the number of active labor market participants in order to address the challenges of an aging society.
Keywords: I28; J18; D04; 330